The Sound of the Oceans - Dan S. Constantinescu (Research Advances in Environment, Geography and Earth Science Vol. 1, 2024)
Following the information of the Whales life and "songs", we analyze the effects of the physical properties of the water on the velocity, intensity and other parameters of the sound. What will be the effect of the sea water of the Black Sea on the phenomenon? The physical data regarding the properties of the sea or ocean water are used in order to analyse the sounds. The properties refer to velocity of the sound in the liquids (sea water), acoustic pressure, acoustic power, experimental values for some sonic parameters. Registered sound offered by the publication National Geographic will be presented. The results are analysed and some conclusions are offered.